MEMBINA RELASI DAMAI ANTARA MAYORITAS DAN MINORITAS (Telaah Kritis atas Peran Negara dan Umat Islam dalam Mengembangkan Demokrasi di Indonesia) - Suprapto, Suprapto (Universitas Islam Negeri Raden Intan Lampung, 2012)
Indonesia is considered the most populous Muslim country in the world that successfully develops democracy. In one hand or another, however, a number of ill treatments of discrimination over those of minorities in this country continuously remains occurring. The minorities have not been fully acquired their rights mainly in relation to religious freedom. This article tries to map out the relationship between majority Muslims and non-Muslim minorities in Indonesia, which involves two important issues: Readiness of majority culture as the main subject and state constitution. Various human rights violations and discrimination experienced by minorities was not solely done by a mere majority, but also by state. It, has systematically issued a potential number of legislation products which marginalizes minorities and favored majority. To protect the rights of citizens from majority groups and state interference, this article puts forward two steps; political advocacy of equality and capacity building for strengthening democratic values. The first step is intended to encourage the more serious attention to and protect the existence of minority groups by issuing laws and regulations that are fair and protected all citizens. While the second step is needed to strengthen democratic values such as liberty, equality and tolerance that has existed within the majority, those of Indonesian Muslims.